Ground and Airborne U.K. Measurements of Nitryl Chloride: An Investigation of the Role of Cl Atom Oxidation at Weybourne Atmospheric Observatory. Issue 20 (19th October 2017) - Bannan, Thomas J.; Bacak, Asan; Le Breton, Michael; Flynn, Michael; Ouyang, Bin; McLeod, Matthew; Jones, Rod; Malkin, Tamsin L.; Whalley, Lisa K.; Heard, Dwayne E.; Bandy, Brian; Khan, M. Anwar H.; et al.
Abstract: Nitryl chloride (ClNO2 ) measurements from the Weybourne Atmospheric Observatory (WAO) are reported from March to April 2013 using a quadruple chemical ionization mass spectrometer with the I − ionization scheme. WAO is a rural coastal site with generally low NO x concentrations, a type of location poorly studied for ClNO2 production. Concentrations of ClNO2 exceeded that of the limit of detection (0.8 ppt) on each night of the campaign, as did concentrations of N2 O5, which was also measured simultaneously with the Cambridge Broadband Cavity Enhanced Absorption Spectrometer. A peak concentration of 65 ppt of ClNO2 is reported here. Vertical profiles of ClNO2 from early‐ to middle‐morning flights in close proximity to WAO are also reported, showing elevated concentrations at low altitude. The photolysis of observed ClNO2 and a box model utilizing the Master Chemical Mechanism modified to include chlorine chemistry was used to calculate Cl atom concentrations. This model utilized numerous VOCs from the second Tropospheric Organic Chemistry project in 2004, at the same location and time of year. From this the relative importance of the oxidation of three groups of measured VOCs (alkanes, alkenes, and alkynes) by OH radicals, Cl atoms, and O3 is compared. Cl atom oxidation was deemed generally insignificant at this time and location for total oxidation due to the much lower concentration of ClNO2 observed, even following the night of greatest ClNO2 production. Key Points: Maximum 65 ppt ClNO2 was recorded during nighttime in the low NO x ground‐based study, with up to 95 ppt measured on an airborne platform Vertical profiles of ClNO2 showed elevated concentrations at the surface with a reduction after ~600 m in height Cl atom oxidation from ClNO2 photolysis was generally insignificant for total oxidation